The world's best street food : where to find it & how to make it. - Lonely Planet Publications (Firm) (Footscray, Vic. ; London : Lonely Planet, 2012)
The street is where you'll find the heart of a cuisine and its culture - somewhere among the taco carts and noodle stalls, the scent of wood fires and the hubbub of fellow diners. Bring the world's greatest street foods to your home with this compendium of classic recipes! 100 authentic recipes with simple, clear instructions for perfect preparation. Glossary of exotic ingredients with easy-to-find alternatives. Evocative profiles of each dish show you where to find the best examples when you're on the road. Written by food writers from around the world with an introduction by Tom Parker Bowles.
Includes index.
Keywords: Street food; Food habits; Cooking